A Porphyrin‐Based Covalent Organic Framework for Metal‐Free Photocatalytic Aerobic Oxidative Coupling of Amines. Issue 58 (23rd September 2021) - He, Huijie; Fang, Xu; Zhai, Dong; Zhou, Wei; Li, Yimeng; Zhao, Wenling; Liu, Chengcheng; Li, Zhen; Deng, Weiqiao
Abstract: Imines are important intermediates in drug synthesis. Photocatalytic aerobic oxidative coupling of amines has been considered as a clean and promising way to produce imines and has attracted great attention. Herein, we designed and synthesized a novel two‐dimensional porphyrin‐based covalent organic framework (Por‐BC‐COF) which adopts an AA stacking mode with excellent crystallinity, high Brunauer–Emmett–Teller surface areas (1200 m 2 g −1 ), wide light absorption range (200–1300 nm) and good stability in a variety of organic solvents. Por‐BC‐COF can be used as a metal‐free heterogeneous photocatalyst for the photocatalytic oxidation of amines to imines under visible light and red light with a high yield (97 %). This work presents a novel and efficient COF photocatalyst in the application of light‐driven organic synthesis. Abstract : A novel two‐dimensional porphyrin ‐based covalent organic framework with excellent crystallinity, high Brunauer–Emmett–Teller surface areas (1200 m 2 g −1 ), wide light absorption range (200‐1300 nm) and suitable band structure was successfully synthesized, and it functioned as an efficient metal‐free heterogeneous photocatalytst for photocatalytic aerobic oxidative coupling of amines under the irradiation of white (400–830 nm), and red light (660–680 nm).